2001
DOI: 10.1063/1.1382848
|View full text |Cite
|
Sign up to set email alerts
|

Growth of aligned carbon nanotubes by plasma-enhanced chemical vapor deposition: Optimization of growth parameters

Abstract: Direct-current plasma-enhanced chemical vapor deposition (CVD) with mixtures of acetylene and ammonia was optimized to synthesize aligned carbon nanotubes (CNTs) on Co- or Ni-covered W wires with regard to wire temperature, wire diameter, gas pressure, and sample bias. A phase diagram of CNT growth was established experimentally in this optimization process. It was revealed by transmission electron microscopy that Co-catalyzed CNTs encapsulated a Co carbide nanoparticle at their tip, disagreeing with a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 22 publications
5
57
0
Order By: Relevance
“…A low acetylene precursor concentration led to a low surface carbon concentration and resulted in limited CNT growth. Tanemura et al [14] reported that at high acetylene concentration, the catalyst surface could be covered or reacted with carbon forming metallic carbide. In that case, C 2 H 2 fragments showed a greater tendency to form graphite or amorphous structures rather than CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…A low acetylene precursor concentration led to a low surface carbon concentration and resulted in limited CNT growth. Tanemura et al [14] reported that at high acetylene concentration, the catalyst surface could be covered or reacted with carbon forming metallic carbide. In that case, C 2 H 2 fragments showed a greater tendency to form graphite or amorphous structures rather than CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Graphite nano-tubes were grown by the PECVD technique on a 500µm thin wire of Pd, as described previously [2][3][4]. Two devices were tested, one with a large reaction chamber (about 3 liter, fig1 a), another with a large vacuum tank connected with a 0.2mm orifice to the small reaction chamber (about 0.3 liter, fig 1b).…”
Section: Methodsmentioning
confidence: 99%
“…The plasma-enhanced chemical vapor deposition (PECVD) method [4] is one of the most efficient production methods of nanotubes or their closed variants graphite nano-Fibers (GNF). The hydrocarbon gas is decomposed at the metal-surface, in the case considered in this paper Pd, leading to excess carbon forming the carbon walls and excess hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a higher electron emission was also observed in CNT grown on carbon fibers compared to CNT on Si, revealing that multiwalled carbon nanotubes (MWCNTs) on carbon fibers has a great potential for emission displays 5 . However, the growth of VACNTs on carbon fibers still has not been deeply explored [16][17][18] as observed on Si and other substrates [19][20][21] . VACNTs have some advantages when compared with the ones grown without any orientation.…”
Section: Introductionmentioning
confidence: 99%